The Carok Culture’s Impact on Law Enforcement in Bangkalan Madura: A Fascinating Case Study - Suyanto, Heru; Bakhtiar, Handar Subhandi (Journal of Judicial Review, 2024)
Carok, a distinct cultural practice, is deeply entrenched in the societal fabric of the Bangkalan Madura community. Historically, it has been their primary method of resolving intricate issues, particularly those centred on wealth, honour, and disputes involving women. This culturally specific method of conflict resolution prompted an in-depth study. The primary objective was to discern to what extent law enforcement officers in Bangkalan Madura were influenced by Carok, a practice so interwoven into the community’s daily life. Furthermore, it aimed to gauge the impact of the Carok culture specifically on the procedures and perspectives of the local police. The findings from this investigation were enlightening. It became evident that the Carok tradition isn’t merely a fringe cultural practice but is, in fact, acknowledged and recognised by a significant portion of the Bangkalan community as a legitimate approach to problem-solving. This deep-rooted cultural acceptance has ramifications for the legal system. When it comes to upholding the law and seeking justice, both the police force and the prosecutor’s office in Bangkalan face a unique set of challenges, unparalleled in communities without such ingrained traditions. These challenges arise because of the profound respect and recognition that the Carok practice commands. As a result, conventional legal methods, designed without the considerations of such cultural nuances, often fall short. They find themselves rendered ineffective, if not entirely redundant, against Carok practitioners. This tension between cultural respect and legal enforcement is a poignant reflection of the complexities of integrating traditional customs within the modern rule of law.